RESEARCH ON STRESS RESILIENCE AMONG HIGH SCHOOL STUDENTS DURING ENTRANCE EXAM PREPARATION (Psychology Travelogs, 2025)
The article explores the structural components of stress resilience among high school students during the period of preparation for entrance examinations. Special attention is given to psychological, social, and academic factors that contribute to increased stress levels, as well as to internal and external resources that support the development of resilience as a key element of students’ psychological well-being. The authors apply empirical research methods, including the Hardiness Questionnaire by S. Maddi and the Spielberger-Hanin State-Trait Anxiety Inventory, to assess stress resilience and anxiety levels among students of Polonne Lyceum № 1.The findings indicate that students’ stress resilience tends to decrease as the exam period approaches, while anxiety indicators show a noticeable increase. The article analyses these dynamics in detail, focusing on the interaction between cognitive, emotional, and behavioral aspects of stress responses. Additionally, the research highlights the importance of supportive educational environments, effective communication with teachers and peers, and the role of self-regulation skills in maintaining resilience.The results of the study confirm the relevance of the problem of developing stress resistance among high school students, since the studied group of high school students has an average level of stress resistance, which indicates the presence of certain skills for overcoming stress, but there is a need to develop flexibility, endurance and self-confidence.Based on the obtained results, the authors propose practical recommendations for school psychologists and social educators aimed at strengthening students’ stress resilience during exam preparation. These include psychoeducational interventions, training in emotional regulation, and the development of adaptive coping strategies to help students maintain psychological balance and perform successfully during high-pressure academic periods.
Keywords: stress tolerance; stress; anxiety; high school students; entrance exams